STRATEGI MARKETING PUBLIC RELATIONS USAHA KECIL MENENGAH (UKM) DALAM MEMPERTAHANKAN LOYALITAS KONSUMEN - Natalina Nilamsari; Vania Aprilia Bianda (Jurnal Pustaka Komunikasi, 2020)
The purpose of this research is 1. To find out how the strategy carried out by the Marketing Public Relations Small And Medium Enterprises (SMEs) Palda Project in maintaining its consumer loyaitas is seen from the increasing competition in the field of business. 2. To know the supporting factors in the implementation of marketing public relations strategy in maintaining the loyalty of consumers. 3. To know the inhibitory factor in the implementation of marketing public relations strategy in maintaining the loyalty of consumers. As for answering questions from this study, this study uses data collection techniques by means of interviews, library studies, and observations. This research methodology uses a qualitative descriptive approach to a social phenomenon. This research uses a paradigm of constructivism. Based on the results of the research, obtained the results of research that marketing public relations strategy of SME Palda Project is to provide attractive offers, as well as by paying special attention to its loyal consumers. And from the results of the study can be said the strategy has been successful in maintaining the loyalty of its consumers.